The Importance of Happiness at Work in Shaping the Performance of Insurance Agents at PT. A Surabaya - Imory Rebecca Jayata Karundeng (International Consortium of Education and Culture Research Studies, 2020)
Employee performance is the result of employee work based on capabilities that can be measured in quantity or quality to carry out certain tasks or work during a specified period of time in accordance with the demands of work and responsibility given to him. While happiness is a latent construct and advantages of the positive aspects as satisfaction and overall quality of human life. Everything that makes an individual feel better and happy with what they have learned. This study aims to determine the correlation between the performances of the insurance agent with happiness in the workplace. This research was conducted on the insurance company PT. A, Surabaya, with participants (N = 50) is an insurance agent who has worked at least one year, once the training, regular meetings and seminars held firm at least 3 times. Data were collected by purposive sampling method. The data collection was carried out by using Performance Scale Ratings which includes five dimensions of performance appraisal, and Happiness Scale by using Oxford Happiness Questionnaire (OHQ). Data were analyzed using Pearson Product Moment parametric statistical analysis. The result of data shows that correlation coefficient was 0.802 with sig 0.000 (p <0.05), which means that there is a positive relationship between performance of the agents in the insurance of PT.A,Surabaya with happiness) in the workplace. Based on these results, happiness is proven to contribute effectively to the performance of an insurance agent in PT. A, Surabaya 64.4%. Descriptively, happiness levels of agent in PT.A,Surabaya was classified as moderate to high and most of the agents have a high level of happiness of 58% and most insurance agent in PT.A, Surabaya had high level of performance at 68 %